Diagnostic value of MR-proANP for heart failure in patients with acute dyspnea：a meta-analysis. Issue 1 (2nd January 2020) - Chen, Yang; Wen, Zheqi; Peng, Long; Liu, Xing; Luo, Yanting; Wu, Bingyuan; Li, Suhua
Abstract: Objectives: This study aimed to review the diagnostic value of mid-regional pro-atrial natriuretic peptide (MR-proANP) for heart failure (HF) in patients who presented to the emergency department (ED) with acute dyspnoea. Methods: Relevant studies were searched on the databases of PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials, with publication date limited to 30 March 2018. Literature identification, quality assessment, data extraction, synthesis, and statistical analysis were performed by standard meta-analysis methods. Individual and pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were calculated. Results: A total of eight studies were retrieved, involving 1562 HF patients and 2249 non-HF patients. The sensitivity for each included study ranged from 80 to 97%, with a pooled sensitivity of 90% (95% CI: 88–91%), while the specificity ranged from 37 to 86%, with a pooled specificity of 68% (95% CI: 66–70%). The pooled PLR for included studies was 2.88(95% CI: 2.12–3.93), with a pooled NLR of 0.16 (95% CI: 0.11–0.24), and a pooled DOR of 18.97 (95% CI: 11.73–30.68). Conclusions: With a decent sensitivity, MR-proANP is a useful biomarker for correctly identifying HF in patients with acute dyspnoea.